2015
DOI: 10.5539/gjhs.v8n3p139
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion Behaviors and Chronic Diseases of Aging in the Elderly People of Iranshahr*- IR Iran

Abstract: Introduction and Aim:Aging is considered as the phenomenon of the day in the health arena of the world and Iran. It is anticipated that there will be an explosion of aging population in Iran in about 2031 and 20-25% of the population will be aged over 60 years. With aging, chronic diseases also increase and diminish the functional ability of older people. On the other hand, increased healthcare costs should be also added to this issue. Health promotion is a concept of process that continues throughout life. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…They families needed to improve health promotion. The goal of health promotion behaviors is to maintain performance, independence and QoL 30 .…”
Section: Discussionmentioning
confidence: 99%
“…They families needed to improve health promotion. The goal of health promotion behaviors is to maintain performance, independence and QoL 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In total, 69.5% of the older people were in the age group of the young elderly (60–69 years old). The mean score of geriatric health promotion behaviors was 6.1 ± 1.87 in the range of 0–11 and 54.9% of them had a score of inappropriate health promotion behavior [23].…”
Section: Discussionmentioning
confidence: 99%
“…Their compliance toward healthpromoting behaviour also decrease. However, in a study by Mofrad, Jahantigh, & Arbabisarjou (2016), they reported that chronic illness had related to one's lifestyle. In their study, the result shows that older adults who have chronic illness perform better on health-promoting behaviour compared than other older adults.…”
Section: Literature Reviewmentioning
confidence: 99%